Clean and Reproducible Voltammetry of Copper Single Crystals with Prominent Facet-Specific Features Using Induction Annealing. Issue 9 (20th September 2021) - Raaijman, Stefan J.; Arulmozhi, Nakkiran; da Silva, Alisson H. M.; Koper, Marc T. M.
Abstract : Although copper is widely used as an electrocatalyst for the CO2 reduction reaction, often little emphasis is placed on identifying exactly the facet distribution of the copper surface. Furthermore, because of differing surface preparation methodologies, reported characaterization voltammograms (where applicable) often vary significantly between laboratories, even for surfaces of supposedly the same orientation. In this work, we describe a surface preparation methodology involving the combination of induction annealing and well-documented electrochemical steps, by which reproducible voltammetry for copper surfaces of different orientations can be obtained. Specifically, we investigated copper surfaces of the three principal orientations: {111}, {100} and {110}, and a representative polycrystalline surface. We compared these surfaces to surfaces reported in the literature prepared via either electropolishing or UHV-standard methodologies, where we find induction preparation to yield improvements in surface quality with respect to electropolished surfaces, though not quite as good as those obtained by UHV-preparation.